Transformations of the sociodemographic profi le in a case of Galician associationism: the Centro Betanzos of Buenos Aires (1945-1979) - Ganza, Denise Rocío (2016)
Th is article aims to contribute to the studies on the Centro Betanzos of Buenos Aires through the development and comparison of the organization sociodemographic profi le at two diff erent moments within its institutional history: the 1945-1949 and the 1975-1979 periods. To this end, I will make use of valuable data registered in the Books of Partners, which will allow the analysis of aspects such as the proportion of male and female members, their ethnic origin, their address location, the weight of family networks or the evolution of the removal of members.